2006
DOI: 10.1080/10656210609484994
|View full text |Cite
|
Sign up to set email alerts
|

Religious Behavior, Personality, and Dimensions of Self-Esteem Among 13- to 15-year-old Adolescents

Abstract: Self-esteem (SE) is widely regarded as an indicator of positive psychological functioning. The empirical evidence for an association between SE and religiosity, although extensive, is ambiguous; some studies have reported a positive association, yet others have failed to detect any significant relationship. The aim of the present paper was to clarify any relationships between the components of SE and several religious behavioral variables among a large sample (N = 3,056) of U.K. adolescents. It was demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
6
0
1
Order By: Relevance
“…More recently, Zhang (1997) reported the internal reliability and construct validity of the school short form to be satisfactory. A literature survey has indicated that the short-form inventory is still in general use, mainly as a measure of global self-esteem (e.g., Delaney & Lee, 1995;Francis, 2005;Francis & Gibbs, 1996;Hills, Francis, & Jennings, 2006;Jones & Francis, 1996;Robbins, Francis, & Kerr, 2007;Sapp, 1994;Stark, Spirito, Lewis, & Hart, 1990;Williams, Francis, & Robbins, 2006), but the factor structure of the instrument appears not to have been investigated. The present study aims to establish whether the school short-form Coopersmith Self-Esteem Inventory has an internal structure that might extend the usefulness of the measure beyond its general application as a measure of global self-esteem.…”
mentioning
confidence: 98%
“…More recently, Zhang (1997) reported the internal reliability and construct validity of the school short form to be satisfactory. A literature survey has indicated that the short-form inventory is still in general use, mainly as a measure of global self-esteem (e.g., Delaney & Lee, 1995;Francis, 2005;Francis & Gibbs, 1996;Hills, Francis, & Jennings, 2006;Jones & Francis, 1996;Robbins, Francis, & Kerr, 2007;Sapp, 1994;Stark, Spirito, Lewis, & Hart, 1990;Williams, Francis, & Robbins, 2006), but the factor structure of the instrument appears not to have been investigated. The present study aims to establish whether the school short-form Coopersmith Self-Esteem Inventory has an internal structure that might extend the usefulness of the measure beyond its general application as a measure of global self-esteem.…”
mentioning
confidence: 98%
“…Previous research has employed the school short-form SEI in relation to physical activity (Delaney & Lee, 1995), effectiveness of counselling (Sapp, 1994) and medical health (Stark et al, 1990). In aspects of Christian religiosity, selfesteem using this measure has been related to God image (Francis, 2005;Robbins et al, 2007), frequency of prayer (Francis & Gibbs, 1996), religious behaviour and personality (Hills et al, 2006), religiosity and religious rejection (Williams et al, 2006).…”
Section: Instrumentmentioning
confidence: 99%
“…A pesar de que la personalidad y la autoestima representan dos de los constructos más estudiados en psicología (Mruk, 2017;Rhodewalt & Tragakis, 2003), la naturaleza teórica de su relación persiste como un tema de debate actual Zeigler-Hill, Besser, Myers, Southard, & Malkin, 2013). Numerosos estudios han explorado este vínculo en distintos contextos como Alemania (Luan et al, 2018;Michaelides et al, 2016), Argentina (Helueni & Enrique, 2015), Brasil (Paiva, Pimente, & Moura, 2017;Schaffhuser, Wagner, Lüdtke, & Allemand, 2014), Bélgica (Rassart, Luyckx, Moons, & Weets, 2014), China (Luk & Bond, 1993;Shi, Liu, Yang, & Wang, 2015;Zeigler-Hill et al, 2015), Eslovaquia (Zitny & Halama, 2011), Estados Unidos (Hair & Graziano, 2003;Shackelford & Michalski, 2011), Estonia (Kaare, Mõttus, & Konstabel, 2009), Filipinas (Chen, Widjaja, & Yen, 2015), Grecia (Tsigilis & Srebauite, 2015), Inglaterra (Hills, Francis, & Jennings, 2006), Indonesia (Chen et al, 2015), Israel (Zeigler-Hill et al, 2015), Japón (Shikishima et al, 2018), Malasia (Keng Cheng & Law, 2015), Noruega (Halvorsen & Heyerdahl, 2006;von Soest, Wagner, Hansen, & Gerstorf, 2017), Portugal (Neto & Mullet, 2004), Suecia (Lawenius & Veisson, 1996), Taiwan (Chen et al, 2015), Tailandia (Chen et al, 2015), o Turquía (Koruklu, 2015). Por lo general, se observa que la autoestima se encuentra fuertemente asociada al neuroticismo (Bleidorn et al, 2016;…”
Section: Introductionunclassified